Analysis of the Thinking Process of Grade V Students of SDI Al Ghaffaar in Solving Mathematical Problems - Fakhintan Ilza Karengga; Abdussakir Abdussakir; Muhammad Amin Nur (Sekolah Tinggi Ilmu Al-Qur'an (SIQ) Amuntai Kalimantan Selatan, 2026)
Math problem-solving skills are essential to train students' logical and analytical thinking, but they are often challenging at the elementary school level due to students' difficulties in understanding initial concepts and digesting the material. This study aims to analyze the thinking process of grade V students of SDI Al Ghaffaar Malang in solving problems of KPK and FPB materials through written tests, student interviews, and documentation. The results showed that the test questions on mathematical problem-solving ability of KPK and FPB materials were tested to be very valid (validity of 90.90%) for grade V students. The main strength of the two students lies in the instrumental understanding in planning and execution of strategies, as evidenced by the high ability to choose methods and apply algorithms. However, students experience significant limitations in relational understanding, particularly in comprehensively understanding problems and verifying results. This pattern of difficulty includes a failure to identify contextual information and conceptual justification, which indicates reasoning is limited to instrumental-procedural aspects. The implications of learning emphasize the need to develop relational understanding through habituation of contextual problem identification, strengthening conceptual reasoning and verification, and optimizing teaching strategies.